Influence of the shape of the cross section and the axial force on the fire resistance of RC columns - Cvetkovska, Meri; Lazarevska, Marijana; Trombeva Gavriloska, Ana (Departman za gradjevinarstvo i geodeziju, Fakultet tehnickih nauka, Novi Sad, 2015)
The influence of the shape and the dimensions of the cross section on the fire resistance of centrically loaded RC columns is presented in this paper. A set of columns with same cross-sectional area, same percentage of reinforcement and different column's side ratio: 30x30 cm, 25x36 cm, 20x45 cm and 60x15 cm (RC wall) are analyzed. Columns are exposed to ISO834 standard fire from all sides and all over the height. In order to define the influence of the load level on the fire resistance of the columns, the intensity of the axial compressive force was varied. For the analyzed series of columns, the fire resistance curves as function of the shape of the cross-section and the intensity of the axial compressive force was designed.
Keywords: RC columns, fire resistance, parametric analysis, fire resistance curves